Educational Leadership in Developing Character-Based Graduate Profiles - Rina Andriani; Ahmad Fahrurrozi; Agus Saefudin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Educational leadership plays a vital role in shaping graduate profiles that combine academic excellence with strong character values. In the Indonesian context, especially in Muhammadiyah schools, character-based education is integrated into academic and spiritual development. This study aims to analyze the concept of educational leadership in developing character-based graduate profiles, the strategies used by school leaders, and the challenges faced during implementation. The results highlight the importance of visionary leadership, curriculum integration, school culture, teacher professionalism, and stakeholder collaboration in strengthening graduates’ character formation